Internet misuse or abuse at workplace a gross misconduct - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bad, 2018)
An employee who abuses or misuses the employer’s internet facilities such as circulating emails that contained abusive language and profanity may be dismissed from employment for gross misconduct. Having said the above, this article seeks to examine the misuse or abuse of workplace internet facilities and its consequence with reference to the Industrial Court’s awards.